Procalcitonin as a diagnostic marker of meningococcal disease in children presenting with fever and a rash. Issue 4 (1st April 2002) - Carrol, E D; Newland, P; Riordan, F A I; Thomson, A P J; Curtis, N; Hart, C A
Abstract : Background: Procalcitonin (PCT), a precursor of calcitonin, is a recognised marker of bacterial sepsis, and high concentrations correlate with the severity of sepsis. PCT has been proposed as an earlier and better diagnostic marker than C reactive protein (CRP) and white cell count (WCC). This comparison has never been reported in the differentiation of meningococcal disease (MCD) in children presenting with a fever and rash. Aim: To determine if PCT might be a useful marker of MCD in children presenting with fever and rash. Methods: PCT, CRP, and WCC were measured on admission in 108 children. Patients were classified into two groups: group I, children with a microbiologically confirmed clinical diagnosis of MCD (n = 64); group II, children with a self limiting illness (n = 44). Median ages were 3.57 (0.07–15.9) versus 1.75 (0.19–14.22) years respectively. Severity of disease in patients with MCD was assessed using the Glasgow Meningococcal Septicaemia Prognostic Score (GMSPS). Results: PCT and CRP values were significantly higher in group I than in group II (median 38.85 v 0.27 ng/ml and 68.35 v 9.25 mg/l; p < 0.0005), but there was no difference in WCC between groups. Sensitivity, specificity, and positive and negative predictive values were higher for PCT than CRP and WCC. In group I, procalcitonin was significantly higher in those with severe disease (GMSPS ≥8). Conclusions: PCT is a more sensitive and specific predictor of MCD than CRP and WCC in children presenting with fever and a rash.